Case Study : Syarikat Muda Osman (SMO) Bookstores Sdn. Bhd / Nor Maisarah Mohd Harun - Mohd Harun, Nor Maisarah (2021)
First and foremost, the company that I had chosen as my main topic for this assignment was Syarikat Muda Osman Sdn. Bhd. (SMO) or now also known as SMO Bookstores. This company was established by late Haji Muda Osman in 1939. The business started with the retail, wholesale and distribution of various types of books and stationery, the company had been involved in distribution and marketing of cigarettes in the vicinity of Pasir Mas district. The company’s mission is to become Book and Stationary Shop Sequence that easy to visit, and having a shop near to you. Its vision is to become a Comfortable Book and Stationary Shop Sequnce, and SMO as source knowledge for Malaysian from the area of distribution of cigarettes. Latest progress, SMO already have 16 branches such as in Kubang Kerian, Pasir Mas, Pasir Puteh, Machang, Tanah Merah, Kuala Krai, Rantau Panjang and includes a branches in Jerteh, Terengganu. The company offers various types of books such as fiction books, non-fiction books, magazines, novels, and stationery. Plus, SMO is also a major supplier of education textbooks for primary schools, secondary schools and institution of higher learner in Kelantan.